Expression of smooth muscle markers in so called malignant fibrous histiocytomas. Issue 9 (27th August 2003) - Hasegawa, T; Hasegawa, F; Hirose, T; Sano, T; Matsuno, Y
Abstract : Aims: To obtain further information regarding the frequency and degree of positivity for smooth muscle markers in a large number of malignant fibrous histiocytomas (MFHs), as an aid to accurate diagnosis. Method: The immunohistochemical features of 100 MFHs were studied and the results were compared with those for 30 leiomyosarcomas. Eighteen cases of MFH with smooth muscle actin (SMA) positivity were examined ultrastructurally. Results: Immunoreactivity for smooth muscle markers, such as desmin, SMA, muscle specific actin (MSA) and h-caldesmon (HCD), which is a specific marker for smooth muscle cells and their tumours, was found in 28, 30, 29, and 29 of 30 leiomyosarcomas. Immunoreactivity for desmin, SMA, MSA, and HCD was found in 17, 30, 14, and two of the MFHs. On electron microscopic examination, approximately half of the cases contained a varying proportion of myofibroblastic cells. The others had only fibroblastic or undifferentiated tumour cells. At least 30% of the cases were found to display features consistent with limited smooth muscle or myofibroblastic differentiation. Conclusion: A large subset of so called MFH in fact shows poorly differentiated smooth muscle or myofibroblastic features, and perhaps such tumours should be regarded as pleomorphic leiomyosarcomas and/or pleomorphic myofibroblastic sarcomas.